INTEGRASI DAN URGENSI METODE TAFSIR TEMATIK DI ERA GENERASI MILINEAL - Dedi Kuswandi; Tamrin; Muliani; Henny Hermayanti (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
The thematic interpretation method is a crucial approach in understanding the Qur'an deeply and relevantly in the modern era. The main issue is how this method can address various contemporary problems by systematically and comprehensively unifying Qur'anic verses under a specific theme. The research method employed in this study is a qualitative-descriptive literature review. Data were collected from various sources, including classical tafsir books, contemporary literature, and related scientific research. Analysis was conducted through critical examination and in-depth interpretation to understand the principles, steps, and benefits of the thematic interpretation method in the modern context. The findings indicate that the thematic interpretation method has high urgency in building a contextual and solution-oriented understanding of the Qur'an concerning current social, cultural, and technological issues. This approach enables the presentation of more organized and easily understood answers for the broader community, thus strengthening the Qur'an's relevance in a dynamic and ever-evolving modern life.